Polycyclic aromatic hydrocarbons in surface seawater at the southern Okhotsk Sea, 2017–2022 - Rodrigo Mundo; Tetsuya Matsunaka; Mutsuo Inoue; Saki Tanaka; Mone Ozawa; Yukiko Taniuchi; Takuya Nakanowatari; Hiromi Kasai; Hideki Kaeriyama; Shizuho Miki; Yuliya Koudryashova; Tatiana Chizhova; et al. (Marine Pollution Bulletin, 2026)

A review of the oceanographic structure and biological productivity in the southern Okhotsk Sea - Rodrigo Mundo; Tetsuya Matsunaka; Takuya Nakanowatari; Yukiko Taniuchi; Mutsuo Inoue; Hiromi Kasai; Kaisei Mashita; Hayata Mitsunushi; Seiya Nagao (Progress in Oceanography, 2024)

140 years-long sedimentary records of PAHs and CN stable isotopes from Ninomiya River, Japan - Rodrigo Mundo; Hisanori Iwai; Shinya Ochiai; Tetsuya Matsunaka; Noriko Hasebe; Seiya Nagao (Marine Pollution Bulletin, 2023)

Deep Water PAH Cycling in the Japan Basin (the Sea of Japan) - Yuliya Koudryashova; Tatiana Chizhova; Mutsuo Inoue; Kazuichi Hayakawa; Seiya Nagao; Evgeniya Marina; Rodrigo Mundo (Journal of Marine Science and Engineering, 2022)
A vertical pattern of fractionated polycyclic aromatic hydrocarbons (PAH) was studied in the Japan Basin in the Sea of Japan. The highest PAH concentration was found in the mesopelagic realm, possibly resulting from deep convection and/or subduction of intermediate water and its biogeochemical setting in the western Japan Basin. Using 226Ra and 228Ra as tracers revealed the PAH load in the open sea from the coastal polluted water. Dissolved PAHs (DPAH, fraction 0.5 µm) at all depths, associated with a predominance of dissolved organic carbon (DOC) over particulate organic carbon (POC). Hydrophobicity was more important for higher-molecular-weight PAHs to be distributed between particles and the solution, while the high Koc of low-molecular-weight PAHs indicated that their partitioning was driven by other factors, such as adsorbing of soot particles. PPAH and DPAH profiles differed from the POC and DOC profiles; nevertheless, a positive moderate correlation was found for DPAH and DOC for depths below the epipelagic, suggesting the similarity of the mechanisms of input of dissolved organic matter and DPAH into the deep interior of the Sea of Japan. The PAH flux calculations showed that biological pumps and overturning circulation contribute almost equally to removing PAHs from the bathypelagic waters of the Japan Basin.